Stress and Temporomandibular Joint - Waleed, Idham; Firas, Mustafa; Chichua, Nino (Caucasus Journal of Health Sciences and Public Health, 2016)
Temporomandibular joint is bilateral synovial articulation between the mandible and temporal bone. TMJ consists of the several parts; bones, the cartilage, capsule and disc. Inside the capsule is lined by synovium, which produces synovial fluid and lubricates the joint. In case of a healthy joint jaw motion is painless, smooth and noiseless. The TMJ is the most often used joint in the body. The temporomandibular joint disorders are very common and ranges from low severity to high severity. To evaluate TMJ by physical examination we usually use palpation, auscultation as well as inspection of the oral cavity and radiographic examination. Many different conditions can affect the TMJ and as a result cause pain and discomfort to patients. Stress and anxiety might be one of the reasons of joint disorders. Some call stress, the disease of the 21st century, it is very common in today’s society and can cause muscle tension, headaches, increased blood pressure, lack of concentration as well as TMJ disorders. Teeth grinding and jaw clenching which is usually caused by stress can be a factor to cause temporomandibular joint disorder. When we are stressed out the trigeminal nerve becomes more active, that creates tension in our jaw muscle, at the same time a lot of pressure is placed on the TMJ and as a result it is causing pain of the joint. As a prevention of TMJ syndrome we have to break bad habits as bighting on objects such as pen or fingernails, avoid large bites while eating, maintain good sleep posture with neck support, visiting doctor if there is a case of grinding teeth at night, using a night split. There are different treatments for Temporomandibular joint disorders that may include wearing mouth protector to prevent bruxism, as well as stress-reducing exercises and medication, also joint blockade therapy and lastly joint replacement surgery. The success of treatment depends on how severe the symptoms are and how well does the patient comply with treatment.